DU PONT SYSTEM ANALYSIS TO ASSESS FINANCIAL PERFORMANCE AT PT ACE HARDWARE TBK PERIOD 2014-2018 - Bani Zamzami (Asosiasi Dosen Muda Indonesia, 2023)
The business world in this era of globalization causes technology to grow rapidly. Therefore, companies are required to run the company's performance better and with a mature strategy, so that the company's goal of achieving high profits can be realized. This writing examines how the financial performance of a company based on the Du Pont System method. In this Du Pont System, it combines asset turnover with profit margins / Net Profit Margin on sales and how much influence they have on Return On Investment (ROI). The purpose of this paper is to determine the financial performance with the Du Pont System PT method. Ace Hardware Tbk Period 2014-2018. The source of this research data is taken directly from the web of PT. Ace Hardware Tbk. From the results of writing company performance measurements using the Du Pont System method at PT.Ace Hardware Tbk for the 2014-2018 period, it can be stated that the company's financial performance is in good condition because it is still above industry standards, the rise and fall of Return On Investment is caused by increased sales not matched by an increase in net profit after tax so that the Net Profit Margin fluctuated over the past five years, and the fluctuating Total Asset Turnover was due to an increase in total assets that was not matched by an increase in sales value.